FACTORS RELATED TO HEALTH PERSONNEL'S COMPLIANCE IN THE IMPLEMENTATION OF HAND HYGIENE IN HOSPITAL - Ida Faridah; Lastri Mei Winarni; Andika Nata Saputra (Universitas Pahlawan Tuanku Tambusai, 2022)
The COVID-19 pandemic and nosocomial infections have made health care facilities a vulnerable place for the development of the COVID-19 virus, so that there are a lot of preventive measures that have become SOPs, especially for health workers in handling patients so as not to contract the COVID-19 virus. The purpose of this study was to determine the factors that influence the compliance of health workers in Serang City Hospital in applying Hand Hygiene. Methods: This study used a quantitative descriptive design. By using purposive sampling technique. The sample size is 105 health workers who meet the criteria. The data collection technique used a questionnaire with the variables of compliance, knowledge, attitude, motivation, supervision, and availability of facilities. The data analysis technique used the Chi-Square test. Results: A total of 64 respondents said that the supervision was good and obedient in applying hand hygiene at the Serang City Hospital. The results of the chi square test obtained p value = 0.019 <0.05. Conclusion: .There is an influence between supervision and compliance of health workers in applying hand hygiene in Serang City Hospital. Keywords: Compliance, Hand Hygiene, Health Workers, Covid-19.